A syringe-based digital algometer with a USB interface: a low-cost alternative to commercially available devices - Frankevich, Stepan; Simmonds, Aryeh; Michaelevski, Izhak; Yakubovich, Daniel (Frontiers in Pain Research, 2025)
Quantitative pain assessment is important for effective pain management. Pain pressure threshold (PPT) and Pain Tolerance (PT) measured through pressure algometry offer valuable tools for quantitative evaluation of nociceptive stimuli. Low-cost algometers, described in literature require complex calibration and lack a digital interface, limiting real-time data acquisition and integration with electronic health record systems. In the current study, we developed a durable and accurate pressure algometer built on the base of a syringe, an Arduino microcontroller and an analog piezoelectric pressure sensor. The PPT values obtained with our device are in good correlation with data obtained utilizing commercially available digital and mechanical algometers. In addition, our device can be easily connected to a computer via a USB, allowing for convenient data storage and analysis. Our results demonstrate the accuracy and reliability of a novel algometry device constructed from readily available materials and requires minimal engineering and programming skills.